Citizen awareness and plastic pollution on beaches in metropolitan Lima, Peru - Chávez-Somoza, Alicia Roxana (2024)
The study addresses the problem of plastic waste pollution on the beaches of Metropolitan Lima, Peru, its negative impact on public health, marine biodiversity and coastal ecosystems, highlighting the relevance of awareness strategies among citizens. The objective was to determine how awareness strategies for citizens are related to plastic waste pollution on Lima beaches. The sample was made up of 120 students from the Toulouse Lautrec School of Higher Education, Lima, Peru, a survey was carried out, where questionnaires based on the study variables were used. The results showed a significant negative correlation (r = -0.66, p < 0.01) between awareness strategies and plastic pollution, indicating that the greater awareness, the less pollution. The cultural, recreational and communication dimensions also presented significant negative correlations with pollution (r = -0.31 and r = -0.39, respectively). These findings underscore the importance of educational and waste management campaigns to mitigate plastic pollution. It is concluded that awareness strategies are effective in reducing plastic pollution, recommending their implementation through public policies and educational programs.